EXPLORATION OF MATHEMATICAL OBJECTS IN THE BALALE’ TRADITION AS AN EFFORT FOR MODULING IN THE DAYAK SALAKO CULTURE AT NYARUMKOP - Dewi Risalah; Vlorenta Prisilla Wiwin; Yudi Darma (USN Kolaka, 2023)
This study aims to explore mathematical objects in the Balale’ tradition of the Dayak Salako tribe in Nyarumkop Village and then integrate them into the Creation of Culture-Based Modules. The research method used is the ethnographic method, and the type of research used is qualitative. The Balale’ tradition is one of the habits of the Nyarumkop farmers when working the rice fields collectively and in rotation. The Balale’ tradition aims to strengthen relations between communities, because the community works together in the fields to complete tasks such as clearing land, planting rice, clearing grass, and harvesting rice. The results of the study show that the Balale’ tradition has a direct mathematical object in the form of facts that lie in the people who join the lale’an members, the concept lies in the process of working the rice fields which are carried out in turns, the principle lies in the mindset of the community in carrying it out and the skills lies in the work technique of each member of Lale’an. This research also contains indirect mathematical objects in the form of discipline shown by Lale’an members in carrying out this tradition. Then it is mathematically integrated into the creation of a culturebased SPLDV Module using mathematical concepts.